2021
DOI: 10.1039/d1ra00257k
|View full text |Cite
|
Sign up to set email alerts
|

pH-responsive viscoelastic supramolecular viscosifiers based on dynamic complexation of zwitterionic octadecylamidopropyl betaine and triamine for hydraulic fracturing applications

Abstract: Viscosity modifying agents are one of the most critical components of hydraulic fracturing fluids, ensuring the efficient transport and deposition of proppant into fissures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 81 publications
(106 reference statements)
0
13
0
Order By: Relevance
“…x kx x ( ) GP( ( ), ( , )) (7) where μ(x) is the mean function, and the covariance function is chosen as a squared exponential kernel, as given in eq 8…”
Section: ■ Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…x kx x ( ) GP( ( ), ( , )) (7) where μ(x) is the mean function, and the covariance function is chosen as a squared exponential kernel, as given in eq 8…”
Section: ■ Theoretical Backgroundmentioning
confidence: 99%
“…In polar solvents, amphiphilic surfactants self-assemble to form supramolecular structures, and one such structure is wormlike micelles (WLMs). Due to its novel rheological properties (i.e., “living” nature), WLMs have found multiple applications in both industry and research areas. Specifically, to meet the various requirements along with the increasing demand for WLM-based products, it is crucial to understand the underlying physiochemical phenomena to accurately predict the rheological behavior of WLMs. Furthermore, given that molecular properties of amphiphiles and reaction conditions significantly affect the properties of WLMs, mathematical models that can predict the effect of altering such parameters on the rheology have been developed.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the development of novel nanostructures of the supramolecular self-assemblies has been widely studied to attain the desired rheological properties. 6 Recently, a complex self-assembly called the dynamic binary complex (DBC) has been synthesized by Liu et al 7 via the complexation between zwitterionic amphiphiles like octadecylamidopropyl betaine (OAPB) and diethylenetriamine (DTA) ions. Specifically, DBCs have unique viscoelastic properties which show sensitivity to the solution conditions like pH.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, DBCs have unique viscoelastic properties which show sensitivity to the solution conditions like pH. In recent studies, 6,7 it was observed that DBCs consist of tubular nanostructures, and the viscoelastic properties of DBCs are determined by the entanglement process of these tubular nanostructures whose cross-sectional dimensions are almost an order of magnitude larger than those of the conventional tubular wormlike micelles (WLMs). It is difficult to rely on the existing imaging techniques like transmission electron microscopy (TEM) to image microgels such as DBCs.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the interactions that may be taking place between the constituent molecules are: hydrogen bonding, π−π stacking, metal-ligand coordination, hydrophobic interactions, halogen bonding and electrostatic interactions [ 34 36 ]. This feature enables responsiveness to an external stimulus such as pH, temperature, salinity, light, redox activation, etc [ 37 40 ]. Furthermore, the weak nature of the forces between the constituents allows for the formation of interesting 3-dimensional structures via a facile self-assembly process [ 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%